Uso de termitas como fuente alternativa al uso de Harina de pescado en la alimentación de alevinos de acarahuazú, Astronotus ocellatus cultivados en corrales - Vela Rodriguez, Edgar Bernardo (2022)
This research work was carried out in the Caserío Libertad, District of Yurimaguas, Province of Alto Amazonas, Department of Loreto. The objective was to evaluate diets including growing termites and productive parameters of Astronotus ocellatus "acarahuazu" fingerlings grown in pens for 90 days. 160 fingerlings of A. ocellatus were stocked, with initial average weight and length of 1.55g and 3.35 cm. The experimental design used was a Completely Random Design (DCA) with 2 treatments (T1= diet without termites, T2= diet with termites), and 4 repetitions per treatment, giving a total of 08 experimental units. A pelleted feed with 32% crude protein was used and a feeding frequency of twice a day was applied. The density used was 1 fish/m2. Biometric samplings were performed every 15 days. At the end of the study, analysis of variance (ANOVA) and Duncan's test at 0.05% probability were performed, finding significant differences between treatments (p<0.05), both in growth and in biological parameters. The physical and chemical parameters obtained were within the optimal range for the cultivation of the species. It is concluded that the T2 treatment had better results in terms of growth (weight and length) and biological parameters of the acarahuazú.